(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: Laboratory investigations has a great role for the detection of pelvic Inflammatory disease among women. Objectives: The purpose of the present study was to see the laboratory profiles of women presented with pelvic inflammatory diseases during reproductive age group. Methodology: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Mymensingh Medical College Hospital, Mymensingh, Bangladesh from January 2008 to June 2009 for a period of one (01) and a half year. Women who were presented with pelvic inflammatory disease (PID) attended at the OPD of gynecology Department at Mymensingh Medical College Hospital, Mymensingh, Bangladesh were selected as study population. Laboratory investigations of each patient were taken and were recorded. Result: A total number of 300 cases were recruited. The mean age with SD was 30.3±9.57 years. In this present study 92(30.7%) patients had haemoglobin level less than 60.0%. The total count of WBC was counted and was found that majority had normal count which was 246(82.0%) cases. Culture of endocervical swab was done in 86 cases of which 34(39.5%) cases showed a growth of bacteria. The most common isolated bacteria was Escherichia coli which was 28(82.0%) cases followed by the growth of Staphylococcus aureus which was in 6(18.0%) cases. Conclusion: In conclusion haemoglobin level, total count of WBC are most commonly found among the women presented with pelvic inflammatory diseases with the predominance of Escherichia coli. Bangladesh Journal of Infectious Diseases June 2021;8(1):3-6